Strategi Guru dalam Menangani Persepsi Siswa Sekolah Dasar bahwa Matematika itu Sulit - Umi Adinda Ramadhani; Sukri; Miftahul Inayah; Mutiara Risty Putri; Zahra Aulia Ramadhani (JURNAL DIKDAS, 2026)
Mathematics is often perceived as a complex subject by elementary school students, which affects their motivation and learning achievement. This study aims to analyze the strategies implemented by teachers to change this perception through adaptive and contextual learning approaches. The research employs a qualitative approach with a case study design involving teachers and students at an elementary school. Data were collected through observations, in depth interviews, and documentation, and then analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that effective strategies include the use of concrete media, the implementation of game-based learning, and the application of contextual approaches that relate the material to students’ daily lives. In addition, positive reinforcement and the creation of a conducive learning environment contribute to increasing students’ confidence in mathematics. Changes in perception are reflected in increased active participation and more positive attitudes among students during the learning process. The discussion highlights that the perception of mathematics as a difficult subject is not only caused by the complexity of the material but also by less varied teaching approaches. Therefore, pedagogical innovation that is responsive to students’ characteristics is needed. The implications of this study emphasize the importance of teachers’ pedagogical competence in creating enjoyable and meaningful learning experiences to reduce the negative stigma toward mathematics from an early age.